PT Tata Makmur Sejahtera's Petty Cash Report Analysis - Thariq Ahmad Rasyid; Dwi Susanti (International Journal of Research in Community Services, 2022)
Companies in the distribution sector cannot be separated from operational activities. These activities incur small nominal costs, requiring a petty cash report. PT. Tata Makmur Sejahtera is one of the companies engaged in this field related to the ability to cover current debts. The company's ability is measured by calculating the ratio using the current ratio and cash ratio. The analysis results show that in January, the current ratio is 0.9616, in February, it is 1.1933, in March, it is 0.8917, and in April, it is 1.0566, and the company's cash ratio is 1.0169. From the calculation of the ratio carried out, it can be concluded that the ability of PT. Tata Makmur Sejahtera covers current debts differently each month. However, the ability to cover current debt during the period studied indicates that the company can cover the current debt.